RELATIONSHIP BETWEEN NATIVE LANGUAGE AND ENGLISH LANGUAGE ACQUISITION: THE CASE OF MERANAW LEARNERS OF ENGLISH - Guimba, Mujahidah; Hadji Faisal, Hamidah; Madale-Unte, Norhayna Eryll; Guimba, Wardah; Alico, Jerryk (Advances in Social Sciences Research Journal, 2019)
ABSTRACT The issue surrounding the relationship between the L1 and L2 has been of great interest among researchers for decades (Cui, n.d.). The newly implemented K+12 Curriculum in the country is also leaning on the proposition that L1 proficiency has a facilitative effect towards second language acquisition among learners. In view of that, the purpose of this study focuses on determining the relationship between L1 and L2 which are Meranaw and English, respectively, in terms of vocabulary skills in the case of fourth year high school students in MSU-UTC. The correlation made use of their scores on the tests that measured their linguistic skill in both languages. The results revealed that most of the respondents are proficient in their native language in terms of synonyms, antonyms, and most especially, context clues. Moreover, respondents with good performance in the English language test also had the largest number. In view of these results, it is inferred that the respondents’ native language proficiency is directly and significantly related to their English language acquisition, which is also supported by the hypothesis tests conducted (p < 0.05). In other words, as native language proficiency increases, English language proficiency also increases. It is recommended that teachers of the recent K+12 Curriculum should properly implement the stipulations of the language curriculum, with the adequate assistance of the government and other authorities, in order to see the positive results of L1 usage in assisting English language acquisition. Conducting further studies is highly encouraged to continually advance knowledge regarding L1 and L2 relationship.